Relative Age Effect on basketball. The case of Chinese professional basketball players - Bonal, José; León-Quismondo, Jairo; Fernández-Luna, Álvaro; Burillo, Pablo; Pérez-González, Benito (Journal of Sport and Health Research, 2026)
The Relative Age (RA) consists of an asymmetry in the birth distribution, involving an overrepresentation of people born in the first months of the year playing different activities. Out of Europe, the background and research on this topic are not as consistent, especially in the sports field. China hosts the Chinese Basketball Association (CBA), which is the main basketball league in Asia. Thus, in the present study, we analyzed the existence of the Relative Age in the CBA during the season 2017/2018. Participants were professional basketball players who participated in the competition (n=318) with an average age of 26.98 ± 4.18 years. The existence of RA was found for all players analyzed (p<0.001). Analyzing the players by their position on the pitch, RA was found at point guards and shooting guards (p<0.001). The greater existence of RA on these positions could be explained by the specific physical and performance requirements of point guards and shooting guards. Our results suggest that China is not an exception in the existing bias about the selection of talent based on the date of birth of players, which generates unequal opportunities in early categories.
Efecto de la edad relativa en baloncesto. El caso de jugadores profesionales de baloncesto de China
La Edad Relativa (RA) consiste en una asimetría en la distribución de la natalidad, que implica una sobrerrepresentación de las personas nacidas en los primeros meses del año. Fuera de Europa, los antecedentes y la investigación sobre este tema no son tan consistentes, especialmente en el campo deportivo. China alberga la Asociación China de Baloncesto (CBA), que es la principal liga de baloncesto de Asia. En el presente estudio analizamos la existencia de Edad Relativa en la CBA durante la temporada 2017/2018. Los participantes fueron jugadores profesionales de baloncesto que tomaron parte de dicha competición (n=318) con una edad promedio de 26,98 ± 4,18 años. Se constató la existencia de RA para todos los jugadores en conjunto (p<0,001). Analizando a los jugadores por su posición en el campo, se encontró RA en bases y escoltas (p<0,001). La mayor manifestación de RA en estas posiciones podría explicarse por los requisitos físicos y de rendimiento específicos de los bases y escoltas. Nuestros resultados sugieren que China no es una excepción en el sesgo existente sobre la selección de talento en función de la fecha de nacimiento de los jugadores, lo que genera desigualdad de oportunidades en las primeras categorías.
Keywords: Relative Age Effect; RAE; basket; birth date; selection bias; talent Identification; Efecto de la Edad Relativa; baloncesto; fecha de nacimiento; sesgo; identificación de talento